Diabetes in pregnancy in associations with perinatal and postneonatal mortality in First Nations and non-Indigenous populations in Quebec, Canada: population-based linked birth cohort study - Lu Chen; Nathalie Auger; Wen-Juan Wang; Lin Xiao; Jill Torrie; Nancy Gros-Louis McHugh; Zhong-Cheng Luo (BMJ Open)
Objective Both pregestational and gestational diabetes mellitus (PGDM, GDM) occur more frequently in First Nations (North American Indians) pregnant women than their non-Indigenous counterparts in Canada. We assessed whether the impacts of PGDM and GDM on perinatal and postneonatal mortality may differ in First Nations versus non-Indigenous populations.Design A population-based linked birth cohort study.Setting and participants 17 090 First Nations and 217 760 non-Indigenous singleton births in 1996–2010, Quebec, Canada.Main outcome measures Relative risks (RR) of perinatal and postneonatal death. Perinatal deaths included stillbirths and neonatal (0–27 days of postnatal life) deaths; postneonatal deaths included infant deaths during 28–364 days of life.Results PGDM and GDM occurred much more frequently in First Nations (3.9% and 10.7%, respectively) versus non-Indigenous (1.1% and 4.8%, respectively) pregnant women. PGDM was associated with an increased risk of perinatal death to a much greater extent in First Nations (RR=5.08[95% CI 2.99 to 8.62], p<0.001; absolute risk (AR)=21.6 [8.6–34.6] per 1000) than in non-Indigenous populations (RR=1.76[1.17, 2.66], p=0.003; AR=4.2[0.2, 8.1] per 1000). PGDM was associated with an increased risk of postneonatal death in non-Indigenous (RR=3.46[1.71, 6.99], p<0.001; AR=2.4[0.1, 4.8] per 1000) but not First Nations (RR=1.16[0.28, 4.77], p=0.35) infants. Adjusting for maternal and pregnancy characteristics, the associations were similar. GDM was not associated with perinatal or postneonatal death in both groups.Conclusions The study is the first to reveal that PGDM may increase the risk of perinatal death to a much greater extent in First Nations versus non-Indigenous populations, but may substantially increase the risk of postneonatal death in non-Indigenous infants only. The underlying causes are unclear and deserve further studies. We speculate that population differences in the quality of glycaemic control in diabetic pregnancies and/or genetic vulnerability to hyperglycaemia’s fetal toxicity may be contributing factors.